2016
DOI: 10.1007/s00265-016-2114-2
|View full text |Cite
|
Sign up to set email alerts
|

Vocal communication regulates sibling competition over food stock

Abstract: Animals resolve conflicts over the share of resources by competing physically or signalling motivation with honest signals of need. In some species, young siblings vocally signal to each other their hunger level and the most vocal individual deters its siblings from competing for the non-divisible food item delivered at the next parental visit. This so-called sibling negotiation for forthcoming food has been studied only in this context. It therefore remains unclear whether siblings could also negotiate access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Second, the differences in HPA activity could be driven by post-natal behavioral cues from parents or siblings. While chick body condition indicated that parents seemed to be meeting the nutritional needs of their chicks at this early age regardless of the supplemental food treatment (but see 4.2), differences in competition from siblings or responsiveness of parents to begging may impact corticosterone secretion (Braasch et al, 2014; Dreiss et al, 2016). Finally, other aspects of interannual environmental variability could modulate the relationship between food availability and corticosterone by imposing additional energetic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the differences in HPA activity could be driven by post-natal behavioral cues from parents or siblings. While chick body condition indicated that parents seemed to be meeting the nutritional needs of their chicks at this early age regardless of the supplemental food treatment (but see 4.2), differences in competition from siblings or responsiveness of parents to begging may impact corticosterone secretion (Braasch et al, 2014; Dreiss et al, 2016). Finally, other aspects of interannual environmental variability could modulate the relationship between food availability and corticosterone by imposing additional energetic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A nestling was assumed to win a dispute if it ended swallowing the food item and to lose it if the food was eaten by its opponent. In the case of food assaults, we also recorded any behaviour by receivers to avoid being robbed, such as concealing food, attempting to hide from the actor, or performing communicative displays (Roulin et al , Dreiss et al ).…”
Section: Methodsmentioning
confidence: 99%
“…This framework also distinguishes song from vocalisations that are socially selected ( sensu Lyon & Montgomerie, 2012) outside the context of sexual competition (e.g. sibling competition in barn owls Tyto alba ; Dreiss et al ., 2016) and vocalisations that may function in cooperation (e.g. chestnut‐crowned babblers Pomatostomus ruficeps ; Crane et al ., 2016), and hence avoids blending the selective processes underlying vocal signal design.…”
Section: Implications For the Traditional Definitions Of Avian Vocalisationsmentioning
confidence: 99%